Assessing the Potential for the Electronics and ICT Manufacturing Industry in Ethiopia - Zhihua Zeng, Douglas; Kayonde, Susan (World Bank, Washington, DC, 2017)
The report includes the analysis of global Information and Communication Technologies (ICT) and electronics value chains, an assessment of Ethiopia’s current and potential participation in these regional and global networks, and an analysis of the country’s competitive positions in specific segments of the sector. The findings of these efforts have been used to provide strategic direction for the development of the sector and to draft an action plan and road map to implement the sectoral strategy in the short, medium, and long term. The analysis shows that the overall electronics and ICT industry is currently playing only a modest role in the Ethiopian economy, with a relatively limited presence of companies and commercial activity. The analysis also illustrates important differences in the competitive position across the various segments analyzed. In conclusion, the analysis has shown that the ICT and electronics industry has potential in Ethiopia, with a presence already emerging in selected segments.